2013
DOI: 10.1111/pcn.12108
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mental well‐being of homeless people in Japan

Abstract: Aim: This study aimed to determine the frequency of low mental well-being and associated factors among homeless people in Japan.Methods: A community-based cross-sectional study was conducted. Data were collected through in-person interviews of 423 homeless persons living in two areas of Tokyo. Mental well-being was assessed using the Japanese version of the World Health OrganizationFive Well-being Index.Results: The overall sample comprised 392 (92.7%) men and 31 (7.3%) women. Average age was 60.6 ± 11.9 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The following question was used to assess perceived instrumental social support: “Can you get help from someone/some people if you have practical problems or are ill?” The two social support measures used in this study are derived from a larger instrument of social support, originally developed by Undén and Orth‐Gomer . Similar questions have been used in earlier studies to measure social support, both in rural and urban populations …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following question was used to assess perceived instrumental social support: “Can you get help from someone/some people if you have practical problems or are ill?” The two social support measures used in this study are derived from a larger instrument of social support, originally developed by Undén and Orth‐Gomer . Similar questions have been used in earlier studies to measure social support, both in rural and urban populations …”
Section: Methodsmentioning
confidence: 99%
“…32 Similar questions have been used in earlier studies to measure social support, both in rural 33 and urban populations. 34,35 The question "Do you have any long-term illness, problems following an accident, any disability or other long-term health problem?" was used for information about long-term illness."…”
mentioning
confidence: 99%
“…That is, social support is significantly correlated with perceived subjective well-being [81]. For example, in Japan [82] it was found that lack of perceived emotional and instrumental social support is associated with mental well-being.…”
Section: Findings and Conclusionmentioning
confidence: 99%
“…Due to their complex economic, social, housing, and physical and mental health needs [ 7 ], people experiencing homelessness tend to have less positive subjective and objective well-being outcomes [ 8 , 9 ]. Few studies that have assessed multidimensional aspects of homeless people’s well-being mainly used cross-sectional [ 9 , 10 ] or qualitative study designs [ 11 ]. Quality of life, psychosocial distress and self-esteem are aspects that some authors have combined to construct an overall multi-dimensional well-being status [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life, psychosocial distress and self-esteem are aspects that some authors have combined to construct an overall multi-dimensional well-being status [ 10 ]. Other authors have used specific well-being indexes, such as the World Health Organization-Five Well-being Index [ 9 ]. Aspects such as food, income, housing, health, friendships, family, romantic relations, physical appearance, and life satisfaction have also been used and analyzed separately to capture specific well-being domains (material, social, and satisfaction domains) well-being of homeless populations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%